Optimal thresholds of risk parameters for gastrointestinal stromal tumors. Issue 1 (January 2020) - Sander, Bjoern; Cameron, Silke; Gunawan, Bastian; Füzesi, Laszlo
Abstract: Background: Gastrointestinal stromal tumors (GIST) are the most frequent mesenchymal neoplasms of the gastrointestinal tract with highly variable potential for relapse. Tumor size and mitotic index (MI) are major risk factors that predict the outcome of GIST patients. Recent risk stratification schemes include some or all of the empirical size thresholds of 2 cm, 5 cm, and 10 cm and MI thresholds of 5 per 50 high-power fields (hpf) and 10 per 50 hpf. However, data that verify these numbers are sparse. Methods: By exhaustive regression tree analysis, maximally selected rank statistics and survival difference analysis with bootstrap sampling on a naive GIST population of 161 patients with a mean follow-up of 44 months, current stratification schemes using tumor size and MI were analyzed herein. Results: /Conclusions : Thresholds that optimally stratify the risk of recurrence are observed at tumor sizes of 4–5 cm and 10–11 cm and at mitotic indices of about 5 per 50 hpf and 10 per 50 hpf, respectively. While these data validate the canonical thresholds for size and MI used in risk stratification of GIST, transition regions as well as differences in the implementation of these thresholds between the different classification schemes proposed in the recent years should be considered when classifying GIST.